Application of Exploratory Factor Analysis (EFA) and Analytic Hierarchy Process (AHP) in Valuation of Urban Residential Land in Quoc Oai Town, Quoc Oai District, Hanoi City - Cuong, Doan Quang; Binh, Tran Quoc (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 2DO - 10.25073/2588-1094/vnuees.4521, 2020)
Land price is essential for land transactions, development of land policy,... Therefore, if the determination of land values is accurate and objective, it will greatly contributes to sustainable, economical and effective use of land resources. In this study, for identifying factors affecting land prices, we had interviewed 100 people, including land users, officials, real estate agents, land management experts. Using exploratory factor analysis, we identified five groups of 16 factors affecting land prices in Quoc Oai Town: location, policy, region, individuality, and environment, where location is the most influential factor group in land prices in Quoc Oai Town. Next, analytic hierarchy process is used to determine weight of each factor and calculate their influence index. The research results have proved the usefulness of combining EFA and AHP in identifying and quantifying factors influencing on land prices for land valuation.